Trait‐based approach to monitoring marine benthic data along 500 km of coastline. Issue 12 (18th September 2019) - Boyé, Aurélien; Thiébaut, Éric; Grall, Jacques; Legendre, Pierre; Broudin, Caroline; Houbin, Céline; Le Garrec, Vincent; Maguer, Marion; Droual, Gabin; Gauthier, Olivier
Abstract: Aim: β diversity and its linkages with ecosystem functioning remain poorly documented. This impedes our capacity to predict biodiversity changes and how they affect ecosystem functioning at scales relevant for conservation. Here, we address the functional implications of ongoing seafloor changes by characterizing at regional scale the taxonomic and functional α and β diversities of benthic habitats currently threatened by biotic homogenization. Location: Western Europe. Methods: Combining a trait‐based approach to benthic community monitoring data covering a 7‐year period and 500 km of coast, we explored the mechanisms governing community assembly in habitats associated with two types of foundation species, intertidal seagrass and subtidal maerl beds, compared to bare sediment at similar tidal level. We assessed their spatial and temporal variability and linked these mechanisms to their repercussions at regional scale through analyses of taxonomic and functional β diversity. Results: Foundation species locally promote taxonomic and functional diversity. Maerl fine‐scale heterogeneity promotes niche diversity and leads to high functional redundancy for the whole subtidal compartment, providing insurance for seafloor functioning. Seagrass high diversity seems more reliant on transient species and is associated with redundancy of only a few functions. Maintaining the seascapes in which seagrass are embedded seems essential to ensure their long‐term functioning. At regional scale, the locally poorer bare sediment harbour similar functional richness as biogenic habitats because of higher within‐habitat β diversity. Main conclusions: Our study reinforces the conservation value of biogenic habitats but highlights that different mechanisms underlie their local diversity, which has implications for the vulnerabilities of their associated communities. Accounting for β diversity at regional scale also stressed a potential underrated conservation value of bare sediment for benthic ecosystem functioning. Coupling trait‐based approaches to monitoring data can help link broad‐scale β diversity to its underlying drivers, bringing local mechanistic understanding closer to the scales at which biodiversity loss and management actions occur.